Le récit retrouvé du vol des reliques de Saint Eudald, martyr d'Ax-les-thermes, par les moines de Ripoll en 978. Edition et commentaire d'un texte fragmentaire - Peloux, Fernand (Miscel·lània litúrgica catalana, 2019)
This paper presents a commented edition of the hagiographic story of the theft of Saint Eudald's relics by the monks of Ripoll, which was discovered in a fragment of an 11th-century legendary preserved in Vic but originally from Ripoll Abbey. This rare witness to the hagiographic activity of Ripoll's scriptorium contains the final part of a text known to exist from a breviary from the close of the Middle Ages and from several summaries from the early modern period. We also discuss Saint Eudald's cult both in southern France and Catalonia from the end of the 10th century, when the monks of Ripoll built their identity on this martyr of Ax-les-Thermes, whose passion in Latin has yet to be discovered.